News writing and reporting for today's media - Itule, Bruce D.; Anderson, Douglas A. (Boston : McGraw-Hill College, 2007)
Designed for introductory news writing and reporting classes, this text focuses on real reporters in real situations. It presents up-to-date coverage of writing principles, with a wide variety of actual news stories from a variety of newspapers. The third edition includes a new chapter on multicultural reporting, expanded coverage of information gathering, and broader coverage of ethics. Its special features are as follows: it uses first-person accounts from working reporters and editors to give students a sense of the excitement of the profession and to show how concepts and principles work in real situations; it provides detailed, comprehensive discussions of the rudiments of news writing and reporting, including coverage on leads, story organization, interviewing
quotations and attribution, and qualities of good writing and gathering of information; it integrates sections on broadcast writing and discusses the differences and similarities between print and broadcast reporting and writing; and it exposes students to a wide variety of current examples of news stories, such as writing excerpts and story sources from small daily newspapers to regional and metropolitan ones. Aspects new to this edition include: a new chapter on multicultural reporting, which stresses how important it is for students to be sensitive to cultures, ethnic groups, religions and lifestyles different from their own; a new chapter on developing a news story, which shows students how to develop a story from day to day and week to week; a chapter on specialized reporting, which now includes coverage of environmental writing and medical and science writing, and features examples and tips from environmental reporter Casey Bukro of "Chicago Tribune"; and it includes broader coverage of ethics and how the journalist's story impacts on society.
Previous ed.: 1997.
Includes index.
1
Keywords: Reporters and reporting; Journalism -- Authorship; Mass media -- Authorship; Report writing